English Learning Strategies Effectiveness to Cope with Students’ Speaking Anxiety at Universitas Negeri Makassar - Anugrah, Ade Surya; Syarifuddin Dollah; Sukardi Weda (International Journal of Language, Education, and Literature, 2025)
Implementing the descriptive qualitative method, the study aims to find out an objective that is to describe the effectiveness of various learning strategies to cope with students’ speaking anxiety. In collecting the study’s data, there are two types of insturements that were impelemmted, the non-participant observations and semi-structured interview sessions. Ten (10) undergraduate students from English Education Program at Universitas Negeri Makassar were volunteered themselves as the study’s research subjects. the result of the study reveals there are six indicators that show how effective the learning strategies are in helping students to cope with speaking anxiety based on the observation and the interview sessions with the study’s subjects. Those indicators are including the students improved academic performance, their increased cognitive engagement, their increased adaptability and transferability, students’ enhancement of metacognitive skills, students’ increased motivation and confidence in speaking, and lastly their positive behavioral changes in students’ speaking activities.